Resveratrol Ameliorates Cardiac Remodeling in a Murine Model of Heart Failure With Preserved Ejection Fraction - Zhang, Liyun; Chen, Juan; Yan, Lianhua; He, Qin; Xie, Han; Chen, Manhua (Frontiers in Pharmacology, 2021)
Objective: Accumulating evidence suggest that resveratrol (RES) could protect against cardiac remodeling induced by several cardiovascular diseases. However, the role of RES in the setting of heart failure with preserved ejection fraction (HFpEF) and the underlying mechanisms remain understood. The aim of this study was to determine whether RES could ameliorate HFpEF-induced cardiac remodeling and its mechanisms. Methods: In vivo, C57BL/6 mice were subjected to either sham or HFpEF model. HFpEF mice model was induced by uninephrectomy surgery and d-aldosterone infusion. RES (10 mg/kg/day, ig) or saline was administered to the mice for four weeks. In vitro, transforming growth factor β1 (TGF-β1) was used to stimulate neonatal rat cardiac fibroblasts (CFs) and Ex-527 was used to inhibit Sirt1 in CFs. Sirt1 and Smad3 expression were measured to explore the underlying mechanisms. Results: HFpEF model mice developed left ventricular hypertrophy, preserved ejection fraction, diastolic dysfunction and pulmonary congestion. HFpEF mice showed infiltration of neutrophils and macrophages into the heart, including increased interleukin (IL)-1β, IL-6 and TNF-α. We also observed elevated M1 macrophages and decreased M2 macrophages which exhibited by increased mRNA expression of M1 markers (iNOS, CD86 and CD80) and decreased mRNA expression of M2 markers (Arg1, CD163 and CD206). Moreover, HFpEF hearts showed excessive oxidative stress. Importantly, HFpEF mice depicted increased collagen-I, III and TGF-β mRNA expression and decreased protein expression of endothelial nitric-oxide synthase (eNOS). And results of western blot reveal that actived TGF-β/Smad3 signaling pathway mediated HFpEF-induced cardiac remodeling. As expected, these HFpEF-induced cardiac remodeling above were reversed when RES was treated. RES decreased Smad3 acetylation and inhibited Smad3 transcriptional activity induced by HFpEF via activating Sirt1. Inhibited Sirt1 with Ex-527 increased Smad3 acetylation, enhanced Smad3 transcriptional activity and offset the protective role of RES on TGF-β-induced cardiac fibroblast-myofibroblast transformation in CFs. Conclusions: Our results suggested that RES exerted protective role against HFpEF-induced adverse cardiac remodeling by reversing myocardial hypertrophy, inflammation, oxidative stress and cardiac fibrosis by decreasing Smad3 acetylation and transcriptional activity via activating Sirt1. And RES is expected to be a novel therapy option for HFpEF patients.